2005
DOI: 10.1111/j.1467-9442.2005.00401.x
|View full text |Cite
|
Sign up to set email alerts
|

International Environmental Agreements and Strategic Voting*

Abstract: This paper explores the outcome of an international environmental agreement when the governments are elected by their citizens. It also considers a voter's incentives for supporting candidates who are less green than she is. In the extreme case of ''global'' pollution, the elected politicians pay no attention to the environment, and the resulting international agreement is totally ineffective. Moreover, if governments cannot negotiate and have to decide noncooperatively (and voters are aware of this), the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
89
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 18 publications
5
89
4
Order By: Relevance
“…He constructed a two-country model where citizens in each country strategically elect a politician who sets and imposes an emission tax on its domestic firms, and showed that citizens may have an incentive to elect a policymaker who is more concerned about the environment than they are. Contrary to the results of Buchholz et al (2005), strategic voting may mitigate the race to the bottom in the noncooperative environmental tax setting. However, Roelfsema's analysis only considers the case where firms produce and sell homogenous goodsà la Cournot and policymakers implement an emission tax as a means of regulation.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…He constructed a two-country model where citizens in each country strategically elect a politician who sets and imposes an emission tax on its domestic firms, and showed that citizens may have an incentive to elect a policymaker who is more concerned about the environment than they are. Contrary to the results of Buchholz et al (2005), strategic voting may mitigate the race to the bottom in the noncooperative environmental tax setting. However, Roelfsema's analysis only considers the case where firms produce and sell homogenous goodsà la Cournot and policymakers implement an emission tax as a means of regulation.…”
Section: Introductionmentioning
confidence: 76%
“…The proposition is closely related to the result of "isolatinist" scenario in Buchholz et al (2005). In the scenario where governments noncooperatively determine their output of domestic products, they show that strategic voting results in a government that assigns less weight to the environment than the median voter.…”
Section: Propositionmentioning
confidence: 91%
See 1 more Smart Citation
“…For instance, Michaelowa and Greiner (1996), Carraro and Siniscalco (1998), Michaelowa (1998), Congleton (2001), Vogt (2002), and Böhringer and Vogt (2004) focus on political processes within a country. The studies by Haffoudhi (2005a and2005b), Buchholz et al (2005), Altamirano-Cabrera et al (2007) and Roelfsma (2007) explore political economy approaches to IEA design and stability.…”
Section: Introductionmentioning
confidence: 99%
“…4 Buchholz et al (2005) provide a theoretical examination of the implications of the electoral process for IEAs, and find significant adverse effects. Based on empirical evidence, Cazals and Sauquet (2015) show that political leaders' levels of commitment to IEAs differ with the timing of elections.…”
Section: Introductionmentioning
confidence: 99%